PENERAPAN IT/ICT DALAM PENDIDIKAN ANDRAGOGI BERBASIS KEARIFAN LOKAL YANG TERINTEGRASI DALAM PEMBELAJARAN SEBAGAI UPAYA PEMBENTUKAN KARAKTER MAHASISWA - Pristi Suhendro (UIN Sumatera Utara Medan, 2014)
Education has two major objectives include (1) the purpose of which is formal, which puts stress on the structuring and formation of private student reasoning students and (2) the purpose of which is material that is putting pressure on implementers as well as the science of life problemsolving skills. The manual labor often complain of college graduates (PT) quality half-hearted. How not to be disappointed if it turns out graduates who scored less formidable, dishonest, quickly bored, can not work teamwork, lack the ability to communicate orally and in writing with a good report. This study linked the values of these soft skills to indigenous people of North Sumatra. Education Andragogy is done based on local wisdom that achievement penginternalisasian character education towards learning can be achieved with either. It distinguishes education andragogy and pedagogy is on (1) the formation of self-image (2) Life Experiences (3) Learning Readiness and (4) Time and Direction Learning. The study of results obtained that andragogy as continuing education activities for adults is a way to learn directly from experience, a re-education process that can reduce social conflicts. Local knowledge-based education model is a model of education that has high relevance for the development of life skills (life skills) by relying on local empowerment and potential ketempilan in each region. Local knowledge-based education is education that teaches students to always be attached to the concrete situations they face. Key Words: Character Education, Andragogy, local wisdom, IT / ICT